Inovasi Olahan Sampah Menjadi Sofa Ecobrick - Yakub, Theresa Lokasari; Yeyen; Amin, Muhammad Nur; Sapar (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
Innovation in processing waste into an sofa. The objectives and benefits of this PKM-K activity are: Generating student motivation to become an entrepreneur in processing plastic bottle waste into ecobrick sofas that are worth selling.  Sofa is a product that is very economically valuable if it can be utilized properly and optimally. This product can add to the aesthetic value of the living room, can be used as decoration and can be used as room accessories. The methods of implementing this program are input, process (production), output, and evaluation. The results of this program are input, conducting market surveys to find out market conditions. Next is a feasibility study of the business to be run. The last stage is the selection of materials and the provision of places as well as facilities and infrastructure to support the production process. Process (production), the process of making sofa starts from the preparation of materials and tools, until the sofa is ready to be marketed. Output, namely sofa crafts that are ready to be used and marketed to consumers. The last is evaluation, that is, this stage is carried out when the production of the sofa has been completed. At this stage, we will review any deficiencies that make consumers uncomfortable using our products. The conclusion of the PKM-K program the innovation of processing waste into Sofa is expected to increase student creativity in processing waste and entrepreneurship with a comprehensive understanding of the concept of entrepreneurship.